Kompetensi Profesional Guru Bahasa Indonesia Kelas IV Sekolah Dasar Katolik - Stefanus Tebajak Henakin; Siprianus See (Jayapangus Press, 2021)
The purpose of this research is to describe the professional competence of Grade IV Indonesian teachers at The Central Ende Catholic Primary School in Ende Regency. Professional competence relates to the teacher's ability to master materials and teaching tasks. This research is a type of descriptive qualitative research. Subjects in this study were Indonesian teachers, principals, and grade IV students. The object of this research is the professional competence of teachers of Bahasa Indonesia subjects. Data collection using interview, observation, and documentation methods. Data analysis is conducted descriptively qualitatively. Based on the results of this study, it is known that the professional competence of Indonesian teachers in grade IV in Catholic primary schools in Central Ende subdistrict is relatively good. Professional competencies that have been mastered by teachers include the ability of teachers in mastering materials, structures, concepts, and scientific mindsets, the ability of teachers in mastering the standard of competence and basic competencies of the Indonesian language, the ability of teachers in developing indonesian language learning materials creatively, and the ability of teachers in developing professionally in a sustainable manner. Thus, it can be concluded that the overall professional competence of indonesian language teachers in grade IV as threatening as Ende Tengah needs to be maintained and also organized efforts to continuously improve the professional competence of teachers in accordance with the development of science and technology.